Heat Stress in Dairy Cattle Alters Lipid Composition of Milk - Z. Liu (Nature Portfolio, 2017)
Abstract Heat stress, potentially affecting both the health of animals and the yield and composition of milk, occurs frequently in tropical, sub-tropical and temperate regions. A simulated acute heat stress experiment was conducted in controlled-climate chambers and milk samples collected before, during and after the heat challenge. Milk lipid composition, surveyed using LC-MS, showed significant changes in triacylglycerol (TAG) and polar lipid profiles. Heat stress (temperature-humidity index up to 84) was associated with a reduction in TAG groups containing short- and medium-chain fatty acids and a concomitant increase in those containing long-chain fatty acids. The abundance of five polar lipid classes including phosphatidylethanolamine, phosphatidylserine, phosphatidylcholine, lysophosphatidylcholine and glucosylceramide, was found to be significantly reduced during heat stress. Lysophosphatidylcholine, showing the greatest reduction in concentration, also displayed a differential response between heat tolerant and heat susceptible cows during heat stress. This phospholipid could be used as a heat stress biomarker for dairy cattle. Changes in TAG profile caused by heat stress are expected to modify the physical properties of milk fat, whereas the reduction of phospholipids may affect the nutritional value of milk. The results are discussed in relation to animal metabolism adaptation in the event of acute heat stress.